2011
DOI: 10.1111/j.1540-6261.2011.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Don't U.S. Issuers Demand European Fees for IPOs?

Abstract: We compare fees charged by investment banks for conducting IPOs in the United States and Europe. In recent years, the "7% solution," as documented by Chen and Ritter (2000), has become even more prevalent in the United States, and is now the norm for IPOs raising up to $250 million. The same banks dominate both markets, but European IPO fees are roughly three percentage points lower, are much more variable, and have been falling. We review explanations for the gap in spreads and find the evidence consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 22 publications
5
58
0
2
Order By: Relevance
“…Apart from some exceptions, they indicated that these negotiations were fruitful and led to a reduced rate (specific reductions that we recorded range from 0.25 to 2% points). This picture complements the comparison of US and European IPO fees by Abrahamson et al (2011) and their finding that the "gross spread" in Europe does not cluster and is substantially lower than the gross spread in the US. Although we did not investigate the precise levels of the ultimate fee, the interviews yielded some evidence that US investment bankers are charging a higher rate than their Dutch peers and that they are less willing to argue over it.…”
Section: Lead Manager Choice and Syndicate Formationsupporting
confidence: 58%
“…Apart from some exceptions, they indicated that these negotiations were fruitful and led to a reduced rate (specific reductions that we recorded range from 0.25 to 2% points). This picture complements the comparison of US and European IPO fees by Abrahamson et al (2011) and their finding that the "gross spread" in Europe does not cluster and is substantially lower than the gross spread in the US. Although we did not investigate the precise levels of the ultimate fee, the interviews yielded some evidence that US investment bankers are charging a higher rate than their Dutch peers and that they are less willing to argue over it.…”
Section: Lead Manager Choice and Syndicate Formationsupporting
confidence: 58%
“…1 Investigating the Italian underwriting market may be instructive, as its institutional setting is similar to most continental European countries, but significantly different from the US market (Abrahamson et al, 2011). In Europe, the price stabilization activity is never mandatory, can be done in the first month of trading and cannot be done above the offering price, as regulated by the Commission Regulation 2273/2003.…”
Section: Institutional Settingmentioning
confidence: 99%
“…In contrast, the NYSE and NASDAQ rankings are strongly correlated. These results provide further evidence of the fragmentation of the IPO underwriting market in Europe, in contrast to integration in the US market (Abrahamson et al ., ).…”
Section: Rankingsmentioning
confidence: 97%
“…When more than one underwriter underwrites an issue, the proceeds are equally split among all lead banks and the IPO count is fractionated (e.g. Aggarwal et al ., ; Abrahamson et al ., ).…”
mentioning
confidence: 97%